Effect of Panchagavya on Seed Germination, Seedling Growth and Nutrient Content of Some Leafy Vegetables - Kala, B. Kamatchi; Eswari, R. Esakiammal Alias (International Journal of Scientific Research in Biological Sciences, 2019)
Improving seed germination can result in increased crop production. Various methods have been used and formulated to increase seed germination and growing efficiency of agricultural crops. Seed priming is one of the successful technologies to maximise the natural potential of seeds in the field. In the present study, growth parameters and nutrient contents were studied in the seeds of three different leafy vegetables such as Amaranthus gangeticus, Hibiscus sabdariffa and Trigonella foenum - graecum primed with 1% solution of Panchagavya at different time intervals. The results showed that seed priming with Panchagavya had a significant effect on seed germination, seedling growth and nutrient contents of all the three selected leafy vegetables.